مشكلات التّربية الجنسية لدى المراهقين في الحلقة الثانية من التعليم الأساسي "دراسة ميدانية في مدينة اللاذقية" - الشمّاس عيسى; الأخرس سمية (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدف البحث إلى تعرّف مشكلات التّربية الجنسية لدى المراهقين في الحلقة الثانية من التعليم الأساسي (طلاب الصف الثامن/ مدينة اللاذقية) وتسعى للإجابة على السؤال الرئيس التالي: ما مشكلات التّربية الجنسية لدى المراهقين في الحلقة الثانية من التعليم الأساسي ؟ ويتفرع عن هذا السؤال الرئيسي الأسئلة الآتية: - ما أكثر المشكلات الناجمة عن نقص التّربية الجنسية لدى المراهقين في الحلقة الثانية من التعليم الأساسي؟ - هل هناك فروق ذات دلالة إحصائية بين إجابات المراهقين في الحلقة الثانية من التعليم الأساسي المتعلقة بتحديدهم للمشكلات الناجمة عن نقص التّربية الجنسية بحسب متغيّرات البحث: الجنس، المستوى التعليمي للأب، المستوى التعليمي للأم؟ - صممت الباحثة استبانة، تم تطبيقهما على عيّنة من طلبة الصف الثامن الأساسي في مدينة اللاذقية، وبلغ عدد أفراد العيّنة (90) طالباً وطالبةً. وقد أظهرت نتائج البحث ما يأتي: - كان من أهم المشكلات الناجمة عن نقص التّربية الجنسية لدى المراهقين مشكلة البحث عن مصادر أخرى للحصول على معلومات جنسية بسبب عدم التحاور مع الأهل، ومشكلة تجنب المشاركة بالمناقشات العلمية المتعلقة بالمواضيع الجنسية، ومشكلة نقص المعلومات الصحيحة عن الأمور الجنسية، ومشكلة الشعور بالخجل الشديد عند الحديث عن الأمور المتعلقة بالجنس. - هناك فروق ذات دلالة إحصائية عند مستوى دلالة 0.05 بين متوسطات إجابات طلبة الحلقة الثانية من التعليم الأساسي فيما يتعلق بالمشكلات الناجمة عن نقص التّربية الجنسية، وفقاً لكل متغيّر من متغيّرات البحث (جنس الطلبة، المستوى التعليمي للأم، المستوى التعليمي للأب). of the students’ gender, father’s educational level ,variant of mother’s educational level. The study aims at specifying the problems of the sexual education with the Adolescents at the Second level of the Basic Education. it answers one basic question: what are the problems of Sexual Education of the Adolescents at the Second Level of the Basic Education? Also the following questions were answered: - What are the problems of Sexual Education of the Adolescents at the Second Level of the Basic Education? - Are there any statical differences among the average answers of the adolescents connected to their definition to the Problems of Sexual Education according to: the gender of the students, father’s educational level ,or mother’s educational level? - The researcher designed a questionnaire which was applied on a sample consisted of eight- Grade basic education students in Lattakia, The sample consists of (90) student, male and female. - The study shows the following findings: The problems coming up from the lack of sexual education with the adolescents are as follows: the problem of searching for other sources to obtain sexual information due to the lack of family discussions, the problem of thinking about sex due to the availability of a great number of mass media exposing and displaying pictures, the deficiency of correct information about sexual matters, and the problem of extreme shyness when talking about sexual topics. Second, the presence of differences that have statistical indication at the significance level (0.05) among the average answers of the adolescents (specimen’s individuals) connected to their definition to the problems coming up from the lack of sexual education according to the variant